Ectoparasites associated with rodents (rodentia) and marsupials (didelphimorphia) from northeastern Argentina : new host and locality records - Benítez Ibalo, Alicia Paola (2020)
Fil: Benítez Ibalo, Alicia Paola. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.